PENGARUH PAJAK TERHADAP BIAYA SEWA DAN PERMINTAAN KAPITAL Kasus : kayu gergajian tropis (THE IMPACT OF TAX ON RENTAL PRICE AND DEMAND FOR CAPITAL Case Study: Tropical Sawn Timber) - Setiasih Irawanti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The objective of this study is to estimate the impact of tax rate on rental price of capital and demand for capital in sawn timbel industry. Sawn timber industry analysed is limited to the sawmills belong to the forest conccession.The study used secondary data. Data analysed are time-series data of interest rate, depreciation, tax rate, and price index of investment, sawn timber production and price.The result of analysis shows that the increase of sawn timber export tax rate at the end of 1989 has caused a rental price of capital increase by approxincalely 4 times, and there was a decrease in the use of capital stock. Demand for equilibrium capital stock of sawn timber industry decreased by Rp 5.077 million (constant price 1983 ) and Rp 5.395 million (constant price 1983) in 1990 and 1991,respectively,or about 50%. it shows that there was a stagnation in the growth of sawn timber industry